2003
DOI: 10.1002/jclp.10242
|View full text |Cite
|
Sign up to set email alerts
|

Using technical innovations in clinical practice: The Drinker's Check‐Up software program

Abstract: Interest in assessing and treating a variety of psychological conditions with software programs is increasing rapidly. This article reviews a software program for problem drinkers entitled the Drinker's Check-Up (DCU) and illustrates its use with three patients. The DCU is based on the principles of brief motivational interventions and can be used as a stand-alone intervention by therapists without expertise in substance abuse or as a prelude to alcohol treatment services. It is the first software program to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…For example, the Computerized Exercise Expert System creates tailored exercise plans for older adults by first gathering information on the person's health status, clinical factors, and exercise determinants that characterize specific barriers or incentives to exercise and then developing individualized exercise prescriptions [80]. Another example of an expert system, Drinker's Check-Up, consists of integrated assessment, feedback, and decision-making modules that are sensitive to the individual's level of readiness for change, ranging from at-risk drinkers to those with alcohol dependence [81]. Such Internet-operated systems hold promise in terms of promoting psychological and behavioral change, although quantitative outcome data are still relatively scarce [76].…”
Section: Internet-operated Therapeutic Softwarementioning
confidence: 99%
“…For example, the Computerized Exercise Expert System creates tailored exercise plans for older adults by first gathering information on the person's health status, clinical factors, and exercise determinants that characterize specific barriers or incentives to exercise and then developing individualized exercise prescriptions [80]. Another example of an expert system, Drinker's Check-Up, consists of integrated assessment, feedback, and decision-making modules that are sensitive to the individual's level of readiness for change, ranging from at-risk drinkers to those with alcohol dependence [81]. Such Internet-operated systems hold promise in terms of promoting psychological and behavioral change, although quantitative outcome data are still relatively scarce [76].…”
Section: Internet-operated Therapeutic Softwarementioning
confidence: 99%
“…One limitation was that older adults appeared less willing or able to use the computer, but this may have been due in part to disabilities (including cognitive impairment) of patients seeking geropsychiatric services or to assumptions of reception staff regarding disabilities. Service issues for further investigation include staff training, optimal procedures to ensure confidentiality (15), software options for alcohol and drug screening, and computer-based interventions (16). Potential benefits of computerized systems include the ability to collect more detailed information than is easily obtained by paper forms, greater validity for sensitive questions, and more time-efficient assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of computerized and Web-based approaches recently have been applied in substance abuse treatment settings and hold tremendous potential for expanding the reach of evidence-based treatment. Web-based approaches have been demonstrated to be efficacious in the delivery of empirically supported nicotine cessation strategies (Glenn & Dallery, 2007;Shiffman, Paty, Rohay, Di Marino, & Gitchell, 2001;Strecher, Shiffman, & West, 2005), motivational enhancement strategies (Ondersma, Chase, Svikis, & Schuster, 2005;Ondersma, Svikis, & Schuster, 2007), moderation management (Hester, Squires, & Delaney, 2005;Squires & Hester, 2004), and HIV prevention strategies (Marsch & Bickel, 2004). In addition, three separate research groups have shown the benefit of using a computerized approach to behavioral therapies (Bickel, Marsch, Buchhalter, & Badger, 2008;Carroll et al, 2008;Kay-Lambkin, Baker, Lewin, & Carr, 2009).…”
Section: Introductionmentioning
confidence: 96%